A clinical review of estimating the accuracy of nasogastric tube insertion depth - Mia Yuliati; Amelia Ganefianty; Nurlaily Afianty; Titis Kurniawan (Journal of Holistic Nursing Science, 2023)
Inserting a nasogastric tube (NGT) is a standard procedure performed by nurses. Assuring the correct position of the tip of the NGT in the stomach is crucial for maximizing the treatment effectiveness and preventing complications due to NGT malposition. While the nose-ear-xiphoid distance is one of the simplest applied methods in estimating the depth of NGT, some studies reported that it is not accurate and is considered no longer safe and increasing the risk for NGT malposition. This literature review aimed to identify the most precise method for determining the NGT insertion depth. The article searched from some electronic sources, namely Sciencedirect and Google Scholar, using "nasogastric tube," "placement," "method," "formula," and "nursing" as the keywords and searching focused on the original research articles published in English between March 2017 – March 2022. Three pieces met the inclusion criteria. These three articles used different definitions and formulas in determining the accurate position of NGT in the stomach. Considering the rate of correct position resulting from the formulas, the xiphoid-ear-nose distance + 10 cm formula was considered the most appropriate formula to be implemented in the daily NGT tube insertion procedure. However, using this formula cannot altogether remove the risk of malposition. Therefore, confirming the position of the NGT using a gastric aspirate pH test or chest x-ray is very recommended. Keywords: Nursing intervention; nutritional status; nasogastric tube; clinical practice; nursing care